2006
DOI: 10.1007/s11242-006-9002-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wet pressing of paper: the three-phase model. Part I: constant air density

Abstract: In this study, we consider a one-dimensional three-phase model describing wet pressing of paper. Part I is devoted to the simplified case in which air is assumed incompressible. In Part II we drop this assumption. The model is formulated in terms of water saturation and void ratio and it uses a material coordinate to describe spatial dependence. It also involves cross or matching conditions between the wet paper and the felt. In mathematical terms, we end up with a coupled system of equations: a nonlinear diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…There exist different approaches to model this problem. Most of the models consider three-phase flow (solid, water, and air) (Bezanovic et al 2006(Bezanovic et al , 2007aHiltunen 1995;Kataja et al 1992). The problem is very complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There exist different approaches to model this problem. Most of the models consider three-phase flow (solid, water, and air) (Bezanovic et al 2006(Bezanovic et al , 2007aHiltunen 1995;Kataja et al 1992). The problem is very complex.…”
mentioning
confidence: 99%
“…In Hiltunen (1995) and Kataja et al (1992), the conservation of mass and momentum is used together with a Lagrangian formulation along displacement characteristic lines (solid flow lines). In Bezanovic et al (2006Bezanovic et al ( , 2007a, the mass balance equations in Lagrangian formulation are used. Moreover, Bezanovic et al (2007b) considers the compressible air case.…”
mentioning
confidence: 99%
“…The material being processed is fed in such a way that the line, which is a continuation of its front end, passes through the axis of rotation of the upper roll, since no additional external forces are required to carry out the capture [4]. Works [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] are devoted to the creation of scientific foundations for the development of roller squeezing machines and the improvement of their parameters. At the same time, it is observed that in the listed works, mathematical models of curves of contact rolls are developed under static interaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its practical importance, the process itself, the changes it causes in the paper structure, and its mechanical properties were intensively studied. 16 On the other hand, the studies on micro- and nanofibrillated celluloses have recently got a great deal of interest because modified wood pulp fibres can be designed to have a controlled structure of cellulose fibril aggregates. In this context, biocomposites are a very promising new range of materials, as discussed in Rantanen and Maloney 7 and Ansari et al.…”
Section: Introductionmentioning
confidence: 99%